Perbandingan Efektivitas Penggunaan Arduino Virtual dan Arduino Real Terhadap Hasil Belajar Siswa pada Mata Pelajaran Informatika Kurikulum Merdeka di SMP Dharma Wiweka - Widiadnyana, Putu; Pown, Nang Lao; Pratiwi, Ni Putu Wika; Yoga, Luh Gede Manik Prascita (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to compare the effectiveness of virtual and real Arduino-based learning at SMP Dharma Wiweka in the implementation of the Merdeka Curriculum. The research employed an experimental design involving two groups of Grade IX students: a virtual group using Tinkercad and a real group using physical Arduino devices. The research instruments consisted of pre-tests, post-tests, and observations of psychomotor skills. Data analysis was conducted using ANOVA, N-gain calculations, and the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach. The results indicate a significant difference between the two groups, with the real Arduino group achieving higher post-test scores and N-gain values (0.65; moderate category) compared to the virtual group (0.47; low–moderate category). The ANOVA results further support this finding, with a p-value of 0.004 < 0.05. The PLS-SEM analysis reveals that learning effectiveness does not have a significant direct effect on learning outcomes (); instead, learning outcomes are more strongly influenced by the type of learning media used. Therefore, real Arduino-based learning is more effective in improving students’ learning outcomes and skills than virtual simulation-based learning. The research outputs include an Arduino teaching module aligned with the Merdeka Curriculum.